2004 Annual Conference Proceedings
DOI: 10.18260/1-2--13362
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit Of Outreach To Engineering Students

Abstract: Engineering K-12 education outreach programs provide a unique opportunity for undergraduate engineers to develop communication and leadership skills as well as build self-confidence. Recently, there has been an engineering education outreach surge at many universities across the country. While the main goal of these programs is to assist educators in incorporating engineering into the K-12 curriculum, there are offshoot benefits to the undergraduate students who participate in outreach efforts, especially fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Participation in outreach events helps undergraduate engineers to strengthen communication and leadership skills and build self-confidence (identity value, competence, and belief in ability) while enhancing their undergraduate experience and sense of civic responsibility [28]. All participants must participate in one STEM Outreach event per year.…”
Section: Stem Outreach Eventsmentioning
confidence: 99%
“…Participation in outreach events helps undergraduate engineers to strengthen communication and leadership skills and build self-confidence (identity value, competence, and belief in ability) while enhancing their undergraduate experience and sense of civic responsibility [28]. All participants must participate in one STEM Outreach event per year.…”
Section: Stem Outreach Eventsmentioning
confidence: 99%
“…Researchers and educators have worked to develop programs and strategies to help combat such negative gender stereotypes in the fields of engineering and technology, while preparing young girls to undertake careers in engineering. Studies have shown that female students, in particular, are attracted to careers with communal and altruistic goals, showing that female students are most interested in the social relevance of the work, exploring career opportunities of engineering fields that link communal goals with engineering practice [5][6][7][8]. Studies have also shown that outreach camps and programs that strive to provide an outlet for like-minded students to interact with each other are a great tool for introducing young students to careers in the STEM fields [9].…”
Section: Introductionmentioning
confidence: 99%